Effect of non-point source runoff and urban sewage on Yaque del Norte River in Dominican Republic. (7th January 2008) - Phillips, Peter; Russell, F. Arturo; Turner, John
A Yaque del Norte, Dominican Republic watershed survey monitored dissolved oxygen, eutrophication from point and non-point sources, and high conductivity resulting from agricultural runoff. The upper mainly forested watershed had good water quality except for untreated sewage from the city of Jarabacoa. The mid-watershed had a deforested landscape, mixed agriculture and the city of Santiago contributing nitrogen and phosphorus. The lower watershed had extensively-irrigated agriculture resulting in appreciably higher conductivity, as well as high nitrogen and phosphorus. Sedimentation from erosion is evident throughout the watershed. Managing the river's land and water resources for all stakeholders is critical.